A design and classification framework for routing protocols in MANETs. (2017) - Kumar, Naresh; Hansdah, R.C.; Maity, Soumyadev
Mobile Ad Hoc Networks (MANETs) are infrastructure-less, self-organising, self-configuring and variable size multihop wireless networks. Many routing protocols have been proposed to deal with routing in such networks. Each routing protocol uses a unique design feature to handle dynamic nature and critical resources of the network. We have put together all the data structure information for routing and routing mechanisms as a design framework to explain the complete design space of the unicast routing protocols in MANETs. A feature of the framework is that the different aspects of routing protocols are well separated. By exploring the design space of the routing protocols in MANETs using the framework, one can possibly better understand the design structures, and can design new routing protocols. To demonstrate the utility of the design framework, we have analysed 27 representative routing protocols of different types, and have categorised them according to the proposed design framework.